Betting on my enemy: Insider trading ahead of hedge fund 13D filings - Duong, Truong; Pi, Shaoting; Sapp, Travis R.A. (Journal of Corporate Finance, 2025)
Corporate insiders often become aware of hedge fund attention prior to a 13D filing. We find abnormal buying activity by insiders in the months leading up to hedge fund 13D filings. Whereas 13D announcement abnormal returns are 7.72 %, profits to insiders who buy average 12.09 %. Insider buying is not linked to common firm characteristics that predict activist targeting. Our findings indicate that insiders are benefiting from private knowledge that their firm has become the focus of hedge fund activism, and sometimes this knowledge comes directly from the activist. However, insiders largely refrain from trading when there is formal communication with the activist. Profits to insiders who buy when there are no talks prior to the 13D filing are 14.49 %, triple the amount for insiders who have had early talks with the hedge fund. Insider trading is linked to indicators of poor corporate culture, but not related to outcomes of activism campaigns.